Strategi Penguatan Moral Siswa di Sekolah (Study Deskriptif Tentang Penguatan Nilai Moral Siswa Melalui Program Sekolah di SDN 4 Cakranegara Mataram) - Sutisna, Deni; Anar, Ashar Pajarungi; Indraswati, Dyah; Nursaptini, Nursaptini; Widodo, Arif (Institut Agama Islam Negeri (IAIN) Curup, 2020)
This study aims to examine how strategies to strengthen student morale through school programs. In analyzing the problem, this study used a descriptive method with observation, interview and documentation study techniques. Some of the findings obtained from the research show that students' moral strengthening strategies are implemented in several aspects; first on the vision and mission of the school where the school sets the vision and mission and goals of the school that imply the values of faith, piety and religion in order to strengthen student morale, secondly in activities both in activities within the school environment or activities outside the school environment related to activities religious values in order to increase religious value, the third application of teacher exemplary aims to provide good moral examples for students so that students learn from existing models, namely teachers, fourth on school facilities and infrastructure, fifth on school rules arranged based on vision mission and school objectives. The results of the research show that this strategy is quite successful in strengthening student morale. There are several findings that can hinder the success of the application of students' moral values, such as: the number of students who are not balanced with the number of classes, the number of teachers who are less than ideal, the utilization of facilities is not optimal, the lack of commitment of the school community, especially the lack of cooperation between parents in strengthening efforts. student morale